Hubungan Stres Akademik dengan Perilaku Emotional Eating pada Siswa SMA di Salatiga - Melanike, Melanike (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study is to examine the relationship between academic stress and emotional eating behavior among high school students in Salatiga. This research employs a quantitative approach with a correlational design. The sample consisted of 105 students selected through an accidental sampling technique. Data were collected using two psychological instruments: the Educational Stress Scale for Adolescents (ESSA) to assess the level of academic stress, and the Dutch Eating Behavior Questionnaire (DEBQ) to measure emotional eating behavior. Data were analyzed using Spearmans Rho correlation test through IBM SPSS Statistics version 24.00. The findings indicate that there is no significant relationship between academic stress and emotional eating. However, the descriptive analysis reveals that a large number of students experience high levels of academic stress, and most students fall into the moderate category of emotional eating. These findings suggest that although no statistical correlation was found, both academic stress and emotional eating are prevalent phenomena among students. Therefore, it is important for parents and teachers to support students in healthily regulating their emotions and to be more aware of their psychological well-being.